Topical Review: Design Considerations When Creating Pediatric Mobile Health Interventions: Applying the IDEAS Framework. (20th October 2018) - Fedele, David A; McConville, Andrew; Moon, Jon; Thomas, J Graham
Abstract: Objective: To present a guiding framework from the perspective of psychologists and technologists to develop effective mobile health (mHealth) interventions for pediatric populations. Methods: This topical review uses the IDEAS framework as an organizational method to summarize current strategies to conceptualize, design, evaluate, and disseminate mHealth interventions. Results: Incorporating theories of behavior change and feedback from target populations are essential when developing mHealth interventions. Following user-centered approaches that fully incorporate end users into design and development stages increases the likelihood that the intervention will be acceptable. Iterative design cycles and prototyping are important steps to gather user feedback to optimize an mHealth intervention. Broad sharing of knowledge and products generated during intervention development also is recommended. Assessment of behavioral principles, intervention components, or a full intervention package should be conducted to evaluate usability and efficacy. Conclusions: Pediatric health-care researchers and clinicians are increasingly using mHealth technology to target health behaviors and improve related outcomes. Pediatric psychologists should consider applying the design strategies outlined in the IDEAS framework to produce and disseminate mHealth interventions tailored to the specific needs of pediatric populations.